(Coleus amboinicus Lour) (Techno Economic Analysis of Production Unit of Torbangun (Coleus amboinicus Lour) Extraxt Powder) - Lukman Junaidi; Tiurlan F. Hutajulu; Dadang Supriatna; Subagja -; Eddy Sapto Hartanto (Balai Besar Industri Agro, 2010)
Torbangun leaves could be extraxted to produce powder whice could be used as a raw material for nutraceutical or medicenal industri. techno economic analysis was conducted to evaluate the financial viability of the production unit of torbangun extract powder. the results of analisis showed that the production unit of torbangun extract powder was very feasible financially. based on the techno economic analysis, the production unit of torbangun extract powder resulted the net present value (NPV) i.e. Rp 650.170.746, internal rate of return (IRR) i.e.36,73% and pay back period i.e. 2,72 years. the break oven point of the production unit of torbangun extract powder was Rp 242.979.681 per year and the based price was Rp 355.239 per kg. the sensitivity analysis showed that the viability of the production unit o torbangun extract powder was very sensitive to the changes in the raw material cost,product price,and yield of the process. on the other hand the changes in the investment cost, electricity, and and working days,ware not sensitive to the viability of production unit of torbangun extract powder.